DISCRIMINATING GEODYNAMICAL REGIMES OF TIN ORE FORMATION USING TRACE ELEMENT COMPOSITION OF CASSITERITE: THE SIKHOTE'ALIN CASE (FAR EASTERN RUSSIA) - Gorelikova N.; Tolosana-Delgado R.; Pawlowsky-Glahn V.; Khanchuk A.; Gonevchuk V. (My University, 2006)
A possible interpretation of the Sikhote'Alin accretion system (Asian margin of the Pacific Ocean) assumes that this region underwent an alternation of subduction and transform tectogenesis (here called the tectogenetic switch hypothesis). This palaeotectonic model fits well with the observed complexity of ore districts and deposits of the region. In this contribution, several statistical analyses are applied to a compositional dataset of trace elements in cassiterite obtained from this area. The goal is to assess the reliability of the tectogenetic switch hypothesis, based solely on cassiterite compositional information. First, biplots are used to get an insight into the variability of the data. Secondly, cluster analysis is applied to detect the existence of natural groups of samples, without using the existing geological information. Finally, discriminant analysis uncovers the main differences in the composition of cassiterite from the different groups obtained. Results highlight the contrast between areas formed under different tectogenetic environments, being subduction-related cassiterite richer in siderophile elements (In, Fe, Sc, W, Cr) and transform-related cassiterite richer in lithophile elements (Mn, Zr). Further natural groups discriminate cassiterite samples depending on their V/Be ratio, which might be related to the age of the deposit. These results suggest that sources of ore magmas and fluids within the region might have a mixed or varied mantle-crust origin and support the tectogenetic switch assumption. © The Geological Society of London 2006.